Immunomodulatory effect of cryopreserved platelets: altered BDCA3+ dendritic cell maturation and activation in vitro. Issue 12 (16th September 2017) - Ki, Katrina K.; Johnson, Lacey; Faddy, Helen M.; Flower, Robert L.; Marks, Denese C.; Dean, Melinda M.
Abstract : BACKGROUND: Cryopreservation of platelets (PLTs) is useful in remote areas to overcome logistic problems associated with supply and can extend the shelf life to 2 years. During cryopreservation, properties of PLTs are modified. Whether changes in the cryopreserved PLT (CPP) product are associated with modulation of recipients' immune function is unknown. We aimed to characterize the immune profile of myeloid dendritic cells (mDCs) and the specialized blood DC antigen (BDCA)3 + subset after exposure to CPPs. STUDY DESIGN AND METHODS: Using an in vitro whole blood model of transfusion, the effect of CPPs on mDC and BDCA3 + DC surface antigen expression and inflammatory mediator production was examined using flow cytometry. In parallel, polyinosinic:polycytidylic acid (poly(I:C)) or lipopolysaccharide (LPS) was utilized to model processes activated in viral or bacterial infection, respectively. RESULTS: Cryopreserved PLTs had minimal impact on mDC responses but significantly modulated BDCA3 + DC responses in vitro. Exposure to CPPs alone up regulated BDCA3 + DC CD86 expression and suppressed interleukin (IL)‐8, tumor necrosis factor (TNF)‐α, and interferon‐γ inducible protein (IP)‐10 production. In both models of infection‐related processes, exposure to CPPs down regulated BDCA3 + DC expression of CD40, CD80, and CD83 and suppressed BDCA3 + DC production of IL‐8, IL‐12, and TNF‐α. CPPs suppressed CD86 expression in the presence of LPS and IP‐10 and IL‐6 production with poly(I:C). CONCLUSION: Cryopreserved PLTs may be immunosuppressive, and this effect is more evident when processes associated with infection are concurrently activated, especially for BDCA3 + DCs. This suggests that transfusion of CPPs in patients with infection may result in impaired BDCA3 + DC responses.